21=(-2)13g

Simple and best practice solution for 21=(-2)13g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21=(-2)13g equation:


Simplifying
21 = (-2) * 13g

Multiply -2 * 13
21 = -26g

Solving
21 = -26g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '26g' to each side of the equation.
21 + 26g = -26g + 26g

Combine like terms: -26g + 26g = 0
21 + 26g = 0

Add '-21' to each side of the equation.
21 + -21 + 26g = 0 + -21

Combine like terms: 21 + -21 = 0
0 + 26g = 0 + -21
26g = 0 + -21

Combine like terms: 0 + -21 = -21
26g = -21

Divide each side by '26'.
g = -0.8076923077

Simplifying
g = -0.8076923077

See similar equations:

| 17k-13k=12 | | 11=-9y | | -8x+-8=2(3-2x) | | y=9x+75 | | f/28-3=1 | | 9x-33=-6x+27 | | w/11-3=8 | | 18h-16h=16 | | x^2+6x-7=3 | | 81=7y+4 | | 53/4÷25/8= | | (6x+5)2=3x+55 | | 7.3-3y-5.18=-51.9 | | 180-90+(180-4x)=6x | | 9+6x=87 | | c=2(3.14)(20) | | 2x+.428571429=1 | | 17k+3k=20 | | 56226-x+0.1x=10000 | | -10-(-7)+4= | | 4u+16=2(u+6) | | M=6-(-12) | | 6z-5z=10 | | ln(x)+ln(x^2+9)=13 | | 3(3x)+2(5)=69x-500 | | 97=5w+7 | | r=20/2(3.14) | | -4x^2-4a=0 | | 2(v+7)=-6v+30 | | 5(x+2)=3(2x+4) | | (5+2w)w=34 | | 5x-3(4x+6)=8 |

Equations solver categories